Formulasi Sediaan Masker Gel Pell- Off Ekstrak Etanol Daun Kopi Arabika (Coffea Arabica) Sebagai Anti- Aging - Ilsanna Surbakti, Christica; Artha Yuliana Sianipar; Syukur Berkat Waruwu (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
Background: Arabica coffee leaves contain phenolic compounds and flavonoid compounds which act as antioxidants. Purpose: To find out whether arabica coffee leaf extract can be formulated in the form of an anti-aging pell-off gel mask. To find out at what concentration the arabica coffee leaf extract pell-off gel mask provides the best activity. Method: Arabica coffee leaf extract is made by maceration. Extract tested screening. Preparation of pell-off gel masks with concentrations of F0 (blanko), F1 (1%), F2 (3%), F3 (5%). Evaluation of the pell-off mask preparation included preparation stability, homogeneity, PH, irritation to volunteer skin, drying time, viscosity, spreadability, and anti-aging effectiveness using a skin analyzer. Results: Simplicia contains alkaloids, flavonoids, tannins, saponins, phenols, steroids. The resulting pell-off mask preparation of ethanol extract of Arabica coffee leaves is homogeneous, PH 5.1-6.1 stable in 4 weeks storage, does not irritate the skin and takes 22- 30 minutes to dry, spreadability is 5-7.5 cm and viscosity 7500- 27050cp. Conclusion: Arabica coffee leaf ethanol extract pell-off gel mask provides better anti- aging effectiveness for 4 weeks. F3(5%) pell-off gelmask provides better anti-aging effects than other formulas.